Transcriptomic Cross‐Species Analysis of Chronic Liver Disease Reveals Consistent Regulation Between Humans and Mice - Christian H. Holland; Ricardo O. Ramirez Flores; Maiju Myllys; Reham Hassan; Karolina Edlund; Ute Hofmann; Rosemarie Marchan; Cristina Cadenas; Jörg Reinders; Stefan Hoehme; Abdel‐latif Seddek; Steven Dooley; et al. (Hepatology Communications, 2022)
Mouse models are frequently used to study chronic liver diseases (CLDs). To assess their translational relevance, we quantified the similarity of commonly used mouse models to human CLDs based on transcriptome data. Gene‐expression data from 372 patients were compared with data from acute and chronic mouse models consisting of 227 mice, and additionally to nine published gene sets of chronic mouse models. Genes consistently altered in humans and mice were mapped to liver cell types based on single‐cell RNA‐sequencing data and validated by immunostaining. Considering the top differentially expressed genes, the similarity between humans and mice varied among the mouse models and depended on the period of damage induction. The highest recall (0.4) and precision (0.33) were observed for the model with 12‐months damage induction by CCl4 and by a Western diet, respectively. Genes consistently up‐regulated between the chronic CCl4 model and human CLDs were enriched in inflammatory and developmental processes, and mostly mapped to cholangiocytes, macrophages, and endothelial and mesenchymal cells. Down‐regulated genes were enriched in metabolic processes and mapped to hepatocytes. Immunostaining confirmed the regulation of selected genes and their cell type specificity. Genes that were up‐regulated in both acute and chronic models showed higher recall and precision with respect to human CLDs than exclusively acute or chronic genes. Conclusion: Similarly regulated genes in human and mouse CLDs were identified. Despite major interspecies differences, mouse models detected 40% of the genes significantly altered in human CLD. The translational relevance of individual genes can be assessed at https://saezlab.shinyapps.io/liverdiseaseatlas/.